Acute unilateral lung injury secondary to lung reexpansion. Case report - Soneira Pérez, Jorge; Diaz Lara, Yanin; Auza-Santivañez, Jhossmar Cristians; Santos Moreira, José Yair; Pérez O’Farrill, Santiago Nelson; Callizaya Macedo, Giovanni (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Lung reexpansion is a rare complication, generally less than 1%, that can occur after rapid drainage of a pneumothorax or pleural effusion. Its mortality can reach 20%.Clinical case: A 22-year-old female patient reported experiencing dizziness, weakness, vomiting containing food, presence of blood clots and bloody-looking stools, which is why she was taken to the hospital to the emergency department, and underwent surgery for upper digestive bleeding. In its evolution, it presents a picture of acute unilateral lung injury secondary to lung reexpansion when draining a pleural effusion. Medical and ventilatory treatment is imposed and the patient evolves favorably.Conclusions: Lung injury due to lung re-expansion is a rare entity; clinical suspicion is essential to act diligently and thus avoid complications. Good ventilatory management of Respiratory Distress Syndrome is essential, emphasizing protective mechanical ventilation and the appropriate use of PEEP